Respuesta :

Given:

f(x) = 5x - 2

g(x) = 1 - 2x

Let's find (fg)(x).

To solve the function operation, we have:

(fg)(x) = f(x) * g(x)

Thus, we have:

[tex](fg)(x)=(5x-2)(1-2x)[/tex]

Solving further:

Expand using FOIL method, then apply distributive property

[tex]\begin{gathered} (fg)(x)=5x(1-2x)-2(1-2x) \\ \\ (fg)(x)=5x(1)+5x(-2x)-2(1)-2(-2x)_{} \\ \\ (fg)(x)=5x-10x^2-2+4x \\ \\ (fg)(x)=+5x+4x-10x^2-2 \\ \\ (fg)(x)=9x-10x^2-2^{} \end{gathered}[/tex]

ANSWER:

[tex]9x-10x^2-2^{}[/tex]

ACCESS MORE